Effect of harmonic structure design with bimodal grain size distribution on near-threshold fatigue crack propagation in Ti–6Al–4V alloy. (November 2016) - Kikuchi, Shoichi; Imai, Takafumi; Kubozono, Hiroki; Nakai, Yoshikazu; Ota, Mie; Ueno, Akira; Ameyama, Kei
Highlights: Titanium alloy can be fabricated with a bimodal harmonic structure. Harmonic structured titanium alloy exhibits low fatigue crack growth resistance. Harmonic structure reduces the magnitude of roughness-induced crack closure. Fatigue crack preferentially propagates across the network structure of fine grains in the harmonic structure. Abstract: Titanium alloy (Ti–6Al–4V) with a bimodal harmonic structure, which consists of a coarse-grained structure surrounded by a network structure of fine equiaxed grains, has been fabricated by sintering mechanically-milled powders to achieve high strength and good plasticity. To investigate the near-threshold fatigue crack propagation in the harmonic structured Ti–6Al–4V alloy, K -decreasing tests are conducted on disk-shaped compact specimens (ASTM standard) under stress ratios R from 0.1 to 0.8 with a constant- R loading regime in a laboratory atmosphere. The fracture surfaces are observed using scanning electron microscopy (SEM), and crack profiles are analysed using electron backscatter diffraction (EBSD) to discuss the mechanism of the fatigue crack propagation. The crack growth rates d a /d N in the harmonic structured material are constantly higher than those in a material with coarse acicular microstructure under comparable stress intensity range Δ K, while the fatigue thresholds Δ K th are lower. This is attributed to a decrease in the magnitude of roughness-induced crack closure and the effective stress intensity range Δ K eff, th in the harmonic structured Ti–6Al–4V alloy due to the presence of fine grains. Furthermore, in some areas, fatigue cracks do not propagate in the coarse-grained structure with higher fatigue crack growth resistance, but they preferentially propagate across the network structure of fine grains in the harmonic structure.